(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The increase in medical imaging services has a significant impact on healthcare costs. The study analyses the dynamics of a number of medical imaging services in Latvia, Lithuania, and in England for comparison (2012-2016), which shows that the number of medical imaging examinations increases in all the countries covered by the study. Moreover, there are significant differences in the application of those services in Latvia and Lithuania if compared to England, which may indicate to inefficient resource management and differences (or absence) of diagnostic guidelines. The following research methods have been used for the research: monographic or descriptive method and graphical method for visualisation, and analysis of visual information.